2008
DOI: 10.1152/ajprenal.00379.2007
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose mTOR inhibition by rapamycin attenuates progression in anti-thy1-induced chronic glomerulosclerosis of the rat

Abstract: -dose mTOR inhibition by rapamycin attenuates progression in anti-thy1-induced chronic glomerulosclerosis of the rat. Am J Physiol Renal Physiol 294: F440-F449, 2008. First published December 19, 2007 doi:10.1152/ajprenal.00379.2007.-Treatment options in human mesangioproliferative glomerulonephritis/sclerosis, mostly IgA nephropathy, are limited. Progressive mesangioproliferative nephropathy represents a major cause of end-stage kidney disease. The present study explores the efficacy of low-dose mTOR inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 32 publications
(91 reference statements)
2
53
0
Order By: Relevance
“…84 Similar findings were reported in animal models of CKD from other causes, including reduced renal mass from five-sixths nephrectomy, 82 renal obstruction after ureteral ligation, 81,85 and chronic mesangioproliferative glomerulonephritis induced by antiThy1 antibody. 73,86 In summary, mTOR plays an important role in the progression of CKD in a variety of animal models. Available evidence suggests a hypothetical schema to explain the beneficial effects of rapamycin on the progression of CKD ( Figure 3).…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…84 Similar findings were reported in animal models of CKD from other causes, including reduced renal mass from five-sixths nephrectomy, 82 renal obstruction after ureteral ligation, 81,85 and chronic mesangioproliferative glomerulonephritis induced by antiThy1 antibody. 73,86 In summary, mTOR plays an important role in the progression of CKD in a variety of animal models. Available evidence suggests a hypothetical schema to explain the beneficial effects of rapamycin on the progression of CKD ( Figure 3).…”
Section: Diabetic Nephropathymentioning
confidence: 99%
“…Artesunate treatment resulted in decreased collagen-IV protein in lung tissues and decreased collagen-IV mRNA in primary lung fibroblast cells, indicating that the anti-fibrotic effect of artesunate might be involve, at least partially, downregulation collagen-IV expression. MMP-2 and MMP-9 are well-known owing to their ability to degrade collagen-IV, and their increased activity leads to various pulmonary diseases including pulmonary fibrosis (Krämer et al, 2008;Bridle et al, 2009;Korfhagen et al, 2009). MMP-2 and MMP-9 play an important role in the inefficient remodeling of damaged lung tissue (Checa et al, 2008;Yamashita et al, 2011;Song et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In this work, an increase in expression of α-SMA was recorded in kidney of rats injected with anti-Thy1. α-SMA expression is a typical molecular marker of myofibroblasts in many nephropathies [1] . In agreement with the present result, Abbate et al reported that the development of fibrosis in anti-Thy1 treated rat is paralleled by increased expression of α-SMA in the tubulo-interstitial area due to peritubular accumulation of myofibroblasts [24] .…”
Section: Discussionmentioning
confidence: 99%
“…It is used as standard animal model to produce experimental glomerulonephritis which is popularly known in the field of nephrology as anti-Thy1 glomerulonephritis. Glomerulonephritis induced by a single injection of antiThy1 antibody is characterized by an acute and selfresolving disease process, whereas repeated injection of the antibody induces irreversible glomerulosclerosis [1] . Masuda et al studied the pathological process of glomerulonephritis including glomerular capillary damage, and vascular endothelial growth factor (VEGF) after anti-Thy1,1 treatment in rats [2] .…”
Section: Introductionmentioning
confidence: 99%